2008
DOI: 10.1097/ftd.0b013e31816336fd
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Response of Clinical Symptoms and Plasma Olanzapine Concentration, Based on Pharmacogenetics

Abstract: The monitoring of plasma olanzapine concentrations has been found to be an important and useful tool for optimizing psychiatric treatment. The present study investigated the effect that clinical factors, such as smoking and age, and functional polymorphisms of UGT1A4, CYP1A2, and CYP2D6 genes have on plasma olanzapine concentration, as well as the effects of plasma olanzapine concentrations on Japanese schizophrenic patients' clinical symptoms. The subjects included 51 chronic schizophrenic patients whose symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 30 publications
3
40
0
3
Order By: Relevance
“…This result is consistent with the literature (Callaghan et al, 1999;Mauri et al, 2007). Tobacco significantly decreased the olanzapine plasma concentration in our sample, in accordance with current knowledge (Callaghan et al, 1999;Carrillo et al, 2003;Mauri et al, 2007;Nozawa et al, 2008;Patel et al, 2011;Weiss et al, 2005): tobacco has been identified as an inducer of cytochrome P450 1A2, with a consequent multiplication of enzymatic activity by a factor of 2-6 (Carrillo et al, 2003). A negative effect of tea/coffee consumption was also found.…”
Section: Dose-concentration Relationshipsupporting
confidence: 94%
“…This result is consistent with the literature (Callaghan et al, 1999;Mauri et al, 2007). Tobacco significantly decreased the olanzapine plasma concentration in our sample, in accordance with current knowledge (Callaghan et al, 1999;Carrillo et al, 2003;Mauri et al, 2007;Nozawa et al, 2008;Patel et al, 2011;Weiss et al, 2005): tobacco has been identified as an inducer of cytochrome P450 1A2, with a consequent multiplication of enzymatic activity by a factor of 2-6 (Carrillo et al, 2003). A negative effect of tea/coffee consumption was also found.…”
Section: Dose-concentration Relationshipsupporting
confidence: 94%
“…33,34 In one study in Japanese patients, olanzapine concentrations were not affected by CYP1A2 polymorphisms but only by smoking. 35 This finding, however, may not be applicable for Caucasians due to further interethnic genetic differences as discussed previously. 19 The CYP1A2*1F (À163A) polymorphism was associated with higher clearance of the CYP1A2 substrate caffeine in Caucasian smokers 18,19 but not in nonsmokers or in Korean smokers.…”
Section: -Htr2c C-759tmentioning
confidence: 89%
“…[9,10] . In clinical practice, olanzapine showed obvious individual differences in plasma concentrations between patients given a normal dose, which necessitated the reasonable individual dosage, even therapeutic drug monitoring [11,12] . In vivo, olanzapine is metabolized to its 10-and 4'-N-glucuronides via UDP-glucuronosyltransferase (UGT1A4), to 4'-N-desmethyl-olanzapine via CYP1A2, to olanzapine N-oxide via flavin monooxygenase 3 and to 2-hydroxymethylolanzapine via CYP2D6 [2] .…”
Section: Effects Of 22 Cyp2d6 Genetic Variations Newly Identified In mentioning
confidence: 99%